Understanding rice production stagnation in the Philippines: Regional evidence and development implications - Henry A. Bartelet; Alenn Jhulia D. Prodigalidad; Janelle S. Dy; Jan Gabriel N. Manzano (PLoS ONE, 2025)
Despite decades of investment in agricultural research and rice development, the Philippines continues to face stagnation in domestic rice production. This persistent trend, occurring despite a sizable arable land base and large rural workforce, has contributed to the country’s growing reliance on rice imports to meet national food needs. In response, the government has implemented a tariff-based import system designed to fund domestic productivity improvements. While previous studies have explored the technical and environmental constraints affecting rice production, such as irrigation shortfalls, land degradation, and climate variability, few have examined recent national trends using regionally disaggregated data alongside qualitative insights. This study fills that gap by analysing official production statistics from 2013 to 2023 across all regions of the Philippines, complemented by contextual data from farming communities and policy reviews. The results reveal that widespread stagnation is primarily driven by limits to both land expansion and yield growth. However, a handful of regions have significantly increased output in recent years, largely due to targeted public investment in irrigation, improved seed technologies, and institutional support. These cases offer important lessons for policy, while also underscoring the risks posed by climate shocks and competing land uses. By identifying both barriers and enablers of rice sector performance, this research contributes to more regionally responsive and inclusive policy strategies aimed at strengthening food security, rural livelihoods, and agricultural resilience in the face of evolving development challenges.